Insecure attachment patterns at five years. What do they tell us? - Priddis, Lynn; Howieson, N. (Routledge, 2012)
Developmental outcomes for children whose primary caregivers are misattuned but not considered abusive are unclear. This paper argues that if by the pre-school years, insecure patterns of attachment are evident then a continuing dysfunctional attachment relationship is indicated and the likelihood of later difficulties is increased. The current study compared attachment patterns in a cohort of pre-school children from the regular community with concurrent behavioural ratings obtained from caregivers and teachers. The sample was followed up seven years later. At pre-school age, there was no association between teachers or caregiver ratings and pattern of security in the children. By pre-adolescence, children with compulsively insecure patterns showed higher levels of depression on a self-report measure. Ratings by caregivers of the pre-adolescent children did not differentiate the two groups. The paper argues that since caregiver misattunment to the child contributed to the initial problems, emotional difficulties in the pre-adolescent might go unseen.